The cost-effectiveness of limiting federal housing vouchers to use in low-poverty neighborhoods in the United States. (January 2020) - Zafari, Z.; Muennig, P.
Abstract: Objective: Residents of low-income neighborhoods are exposed to relatively higher rates of crime, fewer opportunities to exercise, poorer schools, and few opportunities to eat healthy foods than residents of middle-class neighborhoods. Policies that influence neighborhood context could therefore serve as health interventions. We seek to inform the policy debate over the wisdom of spending health dollars on non-health sectors of the economy by defining the opportunity cost of doing so. Study design: Cost-effectiveness analysis with Markov model and Monte Carlo simulation. Methods: We assess the long-term health and economic benefits of Moving to Opportunity–type housing vouchers vs traditional public housing. Our Markov model draws heavily from decades of follow-up data from a large randomized-controlled trial, from which we make projections about health outcomes and costs. Results: Restricted housing vouchers cost less over the lifetime of recipients than traditional vouchers ($186, 629 [95% credible interval: $148, 856–$229, 235] vs $194, 077 [$153, 831-$240, 904]), while improving health and longevity (19.39 quality-adjusted life years [15.83–21.35] vs 19.16 [15.65–21.03]). Over 99% of the model simulations favored restricted housing vouchers over traditional public housing or non-restrictive vouchers. Conclusions: Restrictive vouchers appear to improve population health, save money, and save lives. Highlights: In the US, billions of dollars are being invested in the non-medical determinants of health. It is unclear whether these investments are cost-effective relative to traditional medical care. We find that restrictive rent vouchers produce much greater health and survival than most medical interventions.